Enrolling in the Closest School or Not? Implications of school choice decisions for active transport to school. (September 2017) - Mandic, Sandra; Sandretto, Susan; García Bengoechea, Enrique; Hopkins, Debbie; Moore, Antoni; Rodda, Judith; Wilson, Gordon
Abstract: Background: Absence of requirements to attend a local school combined with social factors driving school choice make distance to school less important in school choice decisions. This study examined correlates of adolescents' enrolment in the closest school in the absence of school zoning policies. Methods: Adolescents (n=797; age: 15.2±1.4 years; 51.4% boys) from six non-integrated (regular) public secondary schools without school zoning in Dunedin, New Zealand, completed an online survey about school choice. Distance to school was calculated using Geographic Information Systems network analysis. Data were analysed using t-tests, Chi-square tests and mixed effects binary logistic regressions. Results: Overall, 51.3% of adolescents enrolled in the closest school (range across schools: 28.3% to 81.6%). These adolescents had five times higher rates of active transport (46.5% vs. 8.8%) and lower rates of motorised transport to school (40.3% vs. 68.8%) compared to their counterparts (all p<0.05). In a multivariate analysis, enrolment in a co-educational school [OR (95%CI): 4.51 (2.60–7.80)] and choosing school because of its proximity to home [2.29 (1.97–2.66)] were positively associated with enrolment in the closest school, whereas distance to school [0.86 (0.82–0.90)] and negative comments from students at closest school [0.68 (0.47–0.98] were negatively associated. Conclusions: In the absence of school zoning, shorter distance to school, importance of school's proximity to home, co-educational school status, and absence of negative peer feedback were associated with adolescents' enrolment in the closest secondary school. School choice decisions have implications not only for education but also for public health, transport and environmental sustainability. A multi-sector approach and extensive collaboration between educational policy makers, urban designers, health promoters, and community groups is required to reduce the tensions between parental and students' school choice expectations of getting the best education possible and the goal of increasing rates of active transport to school. Graphical abstract: Highlights: Without school zoning, half of adolescents enrolled in the closest school. Distance to school and importance of school's proximity influenced school choice. Co-educational school status and peer feedback were also important. Students attending closest school had five times higher rates of active transport. School choice has implications for education, health, transport and environment.